Relasi Pemberitaan Injil dengan Eskatologi menurut Matius 24:14 - Indriati Tjipto Purnomo (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2021)
Eschatology is a branch of Theology, that focuses on what will happen in the last days of the world and human history, studying a season that will take place in the future, that is a reality that the history of the world and all the human beings would finally reach a consumed end. This is actually a process that is progressing toward an a-by-God-appointed-end. God with all His understanding has decided and determined since eternity. Speaking of the end times means the hope of those who believe because at that time the glorious coming of Christ shall be fulfilled and the established Kingdom of God will be marked with the judgment seat for the living and the dead. At the beginning of Jesus’ ministry, He proclaimed repentance and the Kingdom of God (Matthew 4:17). Mark explained at the start of his ministry, John was imprisoned, and Jesus appeared and proclaimed the Gospel, about the Kingdom of God. He said: “The time is fulfilled, and the Kingdom of God is at hand; repent and believe in the Gospel.” (Mark 1:14-15) The purpose of proclaiming the Gospel is for those who hear it will repent and believe in the Gospel. Jesus clearly showed there is a relevance between sharing the Gospel and eschatology.